2011
DOI: 10.1063/1.3672689
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of red blood cell motions in a microchannel with a diverging and converging bifurcation

Abstract: In microcirculation, red blood cells (RBCs) flowing through bifurcations may deform considerably due to combination of different phenomena that happen at the micro-scale level, such as: attraction effect, high shear, and extensional stress, all of which may influence the rheological properties and flow behavior of blood. Thus, it is important to investigate in detail the behavior of blood flow occurring at both bifurcations and confluences. In the present paper, by using a micro-PTV system, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 39 publications
2
72
2
Order By: Relevance
“…In microfluidic systems and in capillary vessels, the RBCs have a size that is a significant fraction of the size of the channel. Effects due to the discrete size of the cells, such as the formation of a plasma layer (Leble et al 2011, Garcia et al 2012, Pinho et al 2013, plasma skimming (Faivre et al 2006), the Zweifach-Fung effect (Svanes and Zweifach 1968, Fung 1973, Doyeux et al 2011, the Fahraeus effect (Fåhraeus 1929) and the Fahraeus-Lindqvist effect (Fåhraeus and Lindqvist 1931) are relevant. A plasma layer or cell-free layer (CFL) is usually formed near the wall of small vessels due to the migration of red blood cells to the center of the microchannel.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In microfluidic systems and in capillary vessels, the RBCs have a size that is a significant fraction of the size of the channel. Effects due to the discrete size of the cells, such as the formation of a plasma layer (Leble et al 2011, Garcia et al 2012, Pinho et al 2013, plasma skimming (Faivre et al 2006), the Zweifach-Fung effect (Svanes and Zweifach 1968, Fung 1973, Doyeux et al 2011, the Fahraeus effect (Fåhraeus 1929) and the Fahraeus-Lindqvist effect (Fåhraeus and Lindqvist 1931) are relevant. A plasma layer or cell-free layer (CFL) is usually formed near the wall of small vessels due to the migration of red blood cells to the center of the microchannel.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…This phenomenon is due to the existence of a CFL in both inner walls and a consequent formation of a triangular CFL in the region of the confluence apex [10,11]. Faivre et al [12] and Sollier et al [13] have demonstrated that the CFL could be enhanced by using a microchannel containing a constriction followed by sudden expansion to separate plasma from the whole in vitro blood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ishikawa et al [10] and Leble et al [11] have shown the existence of thin CFL in the centre of the microchannel, just downstream of a confluence. This phenomenon is due to the existence of a CFL in both inner walls and a consequent formation of a triangular CFL in the region of the confluence apex [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…6 and 7). The existence of these new CFLs is derived from the confluence geometries that influence the RBCs distribution and trajectories, as was shown by a past study performed in a simple microchannel composed by a single bifurcation followed by a confluence [14].…”
Section: Visualization and Measurement Of The Cell-free Layermentioning
confidence: 89%
“…Past studies made in in vitro in microchannels with a simple divergent and convergent bifurcation that showed a pronounced CFL immediately downstream of the apex of the convergent bifurcation [14]. This interesting result led us to the present work, where the CFL in a microchannel network is investigated by using a high-speed video microscopy system in order to further understand the blood flow behaviour in microvessel networks.…”
Section: Introductionmentioning
confidence: 99%